Foundation mathematics - Mustoe, L. R. (J. Wiley, 1998)
Mathematics is finding ever wider areas of application as we seek to understand more about the way in which the natural world and the man-made environment operate and interact. In addition to the traditional use of mathematical models as design tools and for the prediction of the behaviour of many phenomena, mathematics is increasingly being used to model situations in many other disciplines including finance, management, politics and geography. Foundation Mathematics begins with a concise summary of arithmetic, basic algebra and a discussion of quadratics and cubics, strongly emphasising geometric ideas. Then follow the principles of Euclidean and Cartesian geometry and the concept of proof. Next are trigonometry, further algebra, functions and their inverses. Finally, the concepts of differential and integral calculus are introduced. Each chapter starts with a list of learning objectives and ends with a summary of key points and results. A generous supply of worked examples incorporating motivating applications is designed to build knowledge and skill. The exercises provided range in difficulty to aid consolidation and facilitate revision. Answers to the exercises, some including helpful hints, are placed at the end of each chapter. Foundation Mathematics together with its sequel Mathematics in Engineering and Science take the reader forward, in both content and style, from a level close to UK GCSE mathematics and its international equivalents to first year university-level mathematics. The concise and focused approach will help the student build the necessary confidence to tackle the more advanced ideas of the authors related book Mathematics in Engineering and Science (Wiley, 1998). This no-nonsense textbook will enable students to gain a basic grounding in the foundations of mathematics and will enable them to approach further study with confidence.